PENGARUH SIKAP DAN NORMA SUBJEKTIF TERHADAP KEPUTUSAN MEROKOK MASYARAKAT DI YOGYAKARTA - Dinda Sukmaningrum (Jurnal Aplikasi Bisnis, 2022)
According to the concept of social marketing and the behavior of the consument and the connection with ciggarates products as one of many product that contain additive substance, that’s why ciggarates could make someone who smoke feel addicted. But if we take smoking in a positive way and also if smoking was normatively supported by a lot of peoples, that makes the smoker will continue smoking, otherwise if smoking was taken to a negative ways and not normatively supported, eventually the smoker will stop smoking. The purpose of this analysis is to proof if someone will stop smoking or continue smoking affected by some factor which is contained in the concept of attitude subjective norms. To support the verification, then the reaserch is using samples of 100 people that was consist of 50 active smokers and 50 others has stopped smoking. Because there is no official confirmation of the population, the sample was taken by Acidental Sampling. The data collecting was done by survey using a questionnaire instrument with a closed questionnaire and the answers of survey was using a Likert Scal. When the Data was collected it was analyzed using Fishben metodes, Discrimant analysis that was amplified regretion analysis and double linear correlation. The result of this was differentiating value and has influence the decision to smoke or stop smoking. Key Word : attitude, subjective norms and the decision to smoke